IMPLEMENTASI PROTOTYPE PADA SISTEM APLIKASI PERSURATAN KELURAHAN KEDUNGWUNI BARAT (SIPRAKAT) BERBASIS ANDROID - Fajar Mahardika; Sumantri, Raden Bagus Bambang; Ripai, Rizki (Universitas Methodist Indonesia, 2024)
Every agency needs letters, especially the Village Office, because many people need them for purposes such as moving, getting married, giving birth, etc. West Kedungwuni is one of the sub-districts in Kedungwuni District, Pekalongan Regency, Central Java. Prototyping is used when developing systems. This model produces software prototypes that allow users and developers to interact during the information system development process. After completing all research stages, the system created can meet the needs stated in the problem formulation and can assist in managing incoming and outgoing mail in West Kedungwuni District by integrating the database with the Mobile application. Results: 1. Can help in managing incoming and outgoing mail in West Kedungwuni District. 2. Process of distributing incoming and outgoing letters in West Kedungwuni District